1987
DOI: 10.1007/bf00692841
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of glial- and neuronal-associated antigens in human tumors of the central and peripheral nervous system

Abstract: The immunoreactivity of a panel of poly- and monoclonal antibodies raised against different glial and neuronal antigens was investigated in paraffin-embedded specimens of 116 human tumors of the central and peripheral nervous system. We used antibodies against the HNK-1 epitope, which is shared between natural killer cells and the nervous system, glial fibrillary acidic protein (GFAP), vimentin, neurofilaments, S-100 protein, neuron-specific enolase (NSE) and myelin basic protein (MBP). HNK-1 immunoreactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 105 publications
0
14
1
Order By: Relevance
“…2). However, one must be cautious in judgement of a Contrary to reports (5,12,34) of positive immunoreaction against S-IOO protein and GFAP in oligodendrogliomas, our study demonstrated only 3 of 36 oligodendrogliomas to be weakly positive for S-100 protein while all were negative for GFAP. Conflicting results concerning the presence (5,12,34) or absence (8,6,41) ofGFAP in oligodendrogliomas have been reported, and remains an unresolved controversy.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…2). However, one must be cautious in judgement of a Contrary to reports (5,12,34) of positive immunoreaction against S-IOO protein and GFAP in oligodendrogliomas, our study demonstrated only 3 of 36 oligodendrogliomas to be weakly positive for S-100 protein while all were negative for GFAP. Conflicting results concerning the presence (5,12,34) or absence (8,6,41) ofGFAP in oligodendrogliomas have been reported, and remains an unresolved controversy.…”
Section: Discussioncontrasting
confidence: 82%
“…Since GFAP is an indication of astrocyte maturation, its absence in anaplastic tumor cells and progenitor cells suggests that poorly differentiated cells are less capable of producing GFAP. However, 2 studies (12,34) indicated that all astrocytomas had a strong GFAP reaction, irrespective of their degree of malignancy.…”
Section: Discussionmentioning
confidence: 95%
“…NSE has also been demonstrated within a variety of non-neural normal tissues, including vascular smooth muscles (HAIMOTO et al, 1985), and within non-neural tumours, for instance undifferentiated carcinomas, carcinomas of the breast and ovary, lymphomas, and germ cell tumours (BONNIN and RUBINSTEIN, 1984;CRAS et al, 1988;VINORES et al, 1987). Because of the more widespread and diffuse reactivity, "NSE seems to be less valuable as an indicator for neuronal differentiation" (REIFENBERGER et al, 1987). The positive reaction of vascular smooth muscle cells with polyclonal anti-NSE was a common feature in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The reactivity with the antibody against NSE within both turnours was strong within areas of the GCTs, and weak or negative within the typical basal cell tumour. This might be an indication of a different metabolism in both areas of the tumour (CRAS et al, 1988;REIFENBERGER et al, 1987). Granular basal cell carcinomas are a distinct GCT entity in man (GHADIALLY, 1988;GILLIET et al, 1973;LEBOIT et al, 1991) and are found to contain cytokeratin (SLOOTWEG et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Speci®cally, tumors in each of the four transgenic lines mentioned above expressed synaptophysin (Fung et al, 1994), whereas the F1B-Tag tumor does not express any of the neuronal markers tested, including synaptophysin and neuronspeci®c enolase (Figure 8). Neither is the F1B-Tag tumor likely to be an oligodendroglioma or choroid plexus papilloma, as it expressed vimentin, which is absent from tumors of the latter types (Reifenberger et al, 1987). Furthermore, the F1B-Tag tumor is unlikely to be an astrocytoma as the mature tumor does not express GFAP.…”
Section: Comparison With Other Primitive Neuroectodermal Tumors In Trmentioning
confidence: 96%